2014
DOI: 10.1073/pnas.1321727111
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf flushing date influences autumnal senescence and next year’s flushing date in two temperate tree species

Abstract: Recent temperature increases have elicited strong phenological shifts in temperate tree species, with subsequent effects on photosynthesis. Here, we assess the impact of advanced leaf flushing in a winter warming experiment on the current year's senescence and next year's leaf flushing dates in two common tree species: Quercus robur L. and Fagus sylvatica L. Results suggest that earlier leaf flushing translated into earlier senescence, thereby partially offsetting the lengthening of the growing season. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
257
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(292 citation statements)
references
References 61 publications
26
257
9
Order By: Relevance
“…Leaf senescence advanced by 20 days in seedlings of F. sylvatica and Q. robur subjected to 6 ºC warmer temperatures during winter and before leaf flushing in early spring, which was attributed to a legacy of much earlier spring flushing in leaves of warmed saplings (Fu et al, 2014). The timing of leaf senescence was positively correlated with previous flushing dates in the long-term European phenological records of both species, indicating that even though recent environmental cues dominated the variability in the phenology of leaf senescence, they could not fully account for it, which led to the hypothesis that leaf senescence could be triggered by the sink limitation that indicates the accumulation of non-structural carbohydrates in the leaves.…”
Section: Environmental Controls Of Leaf Senescence and Fall And The Ementioning
confidence: 99%
“…Leaf senescence advanced by 20 days in seedlings of F. sylvatica and Q. robur subjected to 6 ºC warmer temperatures during winter and before leaf flushing in early spring, which was attributed to a legacy of much earlier spring flushing in leaves of warmed saplings (Fu et al, 2014). The timing of leaf senescence was positively correlated with previous flushing dates in the long-term European phenological records of both species, indicating that even though recent environmental cues dominated the variability in the phenology of leaf senescence, they could not fully account for it, which led to the hypothesis that leaf senescence could be triggered by the sink limitation that indicates the accumulation of non-structural carbohydrates in the leaves.…”
Section: Environmental Controls Of Leaf Senescence and Fall And The Ementioning
confidence: 99%
“…Thus, the timing of autumn senescence is not affected by the timing of spring phenology in the stem of trees over the study region (Table 1 and Figure 5). However, previous authors found that an earlier leaf flushing resulted in an earlier senescence in two tree species of pedunculate oak (Quercus robur L.) and European beech (Fagus sylvatica L.) in Belgium [22]. The timing of autumn senescence was related to the timing of spring bud-burst by using two decades of ground and satellite-based observations of temperate deciduous forest phenology in the northeastern US [23].…”
Section: Relationships Between Start and Ending Of The Growing Seasonmentioning
confidence: 99%
“…A change in the timing of one phase can potentially affect the timing of subsequent phases (Hänninen and Kramer 2007;Fu et al 2014). Hence, the environmental cues driving the timing of each phase are also indirectly involved in the timing of subsequent phases, as described in Fig.…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…However, scarce effort has been directed at modeling the induction of dormancy, which is tightly linked to leaf senescence and cold acclimation and, further, impacts spring phenophases. Another example is the partial dependence of leaf senescence on the timing of budburst (Fu et al 2014), which has not been implemented in models to date (but see Keenan and Richardson 2015). This situation indicates the need for a common framework that is representative of the cyclic nature of phenological events (Figs.…”
Section: How Can We Improve Phenological Models?mentioning
confidence: 99%